2011
DOI: 10.1108/09540911111146944
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of tin pest on the surface of tin‐rich lead‐free alloys

Abstract: PurposeThe purpose of this paper is to investigate tin pest formation in lead‐free alloys.Design/methodology/approachSamples of Sn99.5Ag3.0Cu0.5, Sn99Cu1 and Sn98Cu2 alloys were prepared in four different forms. The first group was prepared using traditional PCB technology and a hand soldering method. The next group of samples was composed of as‐received ingots of these alloys. To check the impact of mechanical treatment on the transformation process, additional cold‐worked and cold‐rolled samples were prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…However, with the recent global introduction of lead-free solders in the electronics industry to replace formerly used Sn-Pb alloys, the potential susceptibility to tin pest at low temperatures has attracted renewed vivid attention. The topic was re-investigated by several groups for typical tin-rich alloys used in electronic soldering applications with the goal of better understanding the factors influencing the start and spread of tin pest and its dependence on alloy components and impurities [5,8,[11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the recent global introduction of lead-free solders in the electronics industry to replace formerly used Sn-Pb alloys, the potential susceptibility to tin pest at low temperatures has attracted renewed vivid attention. The topic was re-investigated by several groups for typical tin-rich alloys used in electronic soldering applications with the goal of better understanding the factors influencing the start and spread of tin pest and its dependence on alloy components and impurities [5,8,[11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that minor impurities in the tin specimens can influence the transformation strongly. Minute concentrations of impurities like Sb, Bi and Pb, each element having an appreciable solid solubility in the tin matrix, can suppress or slow down the transition to gray tin significantly [1,8,[12][13][14][15][16][17], since they hinder lattice expansion by the pinning of dislocations.…”
Section: Introductionmentioning
confidence: 99%
“…As reported earlier, the value of the force used in mechanical treatment is also significant (Skwarek et al, 2011). Joo and Takemoto (2002) also described an increase in the ␣/␤ transformation rate connected to an increase in the cold reduction ratio (i.e.…”
Section: Mechanically Pressed Ingotsmentioning
confidence: 53%
“…This alloy was chosen, on the basis of a previous report, as the most prone to tin pest formation (Skwarek et al, 2011). The samples were then divided into four groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation